Comparison Of Knowledge And Attitudes Of Pregnant Women About Stunting Using Booklet Media And Audiovisual Media Contents Of My Plate - Sapnita, Sapnita; Hidayat, Wisnu; Sinaga, Taruli Rohana (Sean Institute, 2022)
A World Health Organisation (WHO) report from 2021 states that Universal Health Coverage (UHC) ensures that everyone gets high-quality medical care as and when they need it, without creating any barriers. Of the anticipated 1 billion population, only about 270 million people are expected to get health services between 2000 and 2023. The purpose of this study is to evaluate the job satisfaction of nurses working in inpatient wards of hospitals in 2023 in Banyuasin Regency. This study will be conducted in May 2023. A total of 34 nurses working in the inpatient wards of Banyuasin Regional Hospital were the sample population for this quantitative, cross-sectional study. the sample was 34 respondents, and used complete sampling for sample collection. using questionnaires for data collection and retrieval. Chi-Square statistical test and multiple logistic regression were used in the statistical test analysis, and the findings showed a significant relationship (p-value 0.05) between the variables of incentives (p=0.037), work environment conditions (p=0.001), training (p=0.000), legal protection rights (p=0.002), and rewards (p=0.016). Age (p=0.447), gender (p=0.591), education (p=0.660), length of service (p=0.448), leadership (p=1.000), promotion opportunities (p=0.662), supervision (p=1.000), and punishment (p=0.731) were not correlated with each other. Based on the results of multivariate statistical analysis, the training variable is the most important factor in determining the level of satisfaction of nurses with their work (p=0.003; OR=63.254). It is intended that nursing management in Banyuasin Hospital can protect nurses legally, educate nurses to become competent nurses, pay attention to the quantity of incentives, build a pleasant work environment, and use rewards and punishments to inspire nurses.